THE USE OF MISTAKE BASTER TECHNIQUE TO PROMOTE THE STUDENTS’ WRITING SKILL - Selvi Aprilia; Tahrun Tahrun; Herlina Herlina (Esteem Journal of English Education Study Programme, 2023)
The study aimed to investigate the effectiveness of the Mistake Buster Technique in improving the writing achievement of tenth-grade students at SMK Yayasan Bakti Prabumulih. The objective was to determine whether the use of this technique effectively enhanced the students' ability to write recount paragraphs. An experimental design was employed for this study, specifically a group pretest and posttest design. The population consisted of all tenth-grade students at SMK Yayasan Bakti in the academic year 2021–2022, totaling 60 students. A sample of 28 students was selected using purposive sampling, with 28 students assigned to the experimental group (X TKJ 1) and 32 students to the control group (X TKJ 2). The data were collected through pretests and posttests and analyzed using SPSS 23 software. The results revealed that the experimental group had an average posttest score of 68.03, while the control group had an average posttest score of 61.92. The critical value at a significance level of 0.05 for a one-tailed test with 62 degrees of freedom was 1.699. As the obtained t-value of 13.920 was higher than the t-table value, the null hypothesis was rejected and the alternative hypothesis was accepted. This indicates a significant difference between the tenth-grade students at SMK Yayasan Bakti who were taught using the Mistake Buster Technique for learning to write recount paragraphs and those who were not.